Ecofísiologia da germinação de sementes de espécies frutíferas de ocorrência espontânea em municípios da baixada ocidental maranhense - Gomes, Josilda Junqueira Ayres (2004)
The seed germination physiology of some fruit species from the Baixada Maranhense Ocidental region of Maranhão State: juçara (Euterpe oleracea Mart), bacaba (Oenocarpus distichus Mart), murici (Byrsonima crassifolia (L) Rich), bacurizinho (Rheedia acuminata Mart) was studied through experiments led at the UEMA Farm School - Agrarian Sciences Center in São Luís, and at the Laboratory of Seeds Analysis. The ripe juçara, bacaba, murici and bacurizinho fruits had their pulps removed and, after that, the drying process took place. The bacaba and juçara seeds were split into two batches: in one of them the seeds had their pulps removed and in the other the pulps were kept. Each batch was separated to be conserved at a natural environment, in a refrigerator for 15 and 20 days, and the remainder was used on the germination tests in eight different substrata and it was analized for the bacaba seeds position experiment, in relation to the substratum. For murici seeds, it was led some pre-germinative treatments, sulfuric acid in the concentrations of 25%, 50%, 75% and 100% during 60 minutes, and for the araçá-do-mato, the same concentrations of sulfuric acid during 30 minutes, and maceration for 24 and 48 hours at 42°C in greenhouse and hot water at 80°C, to interrupt the structural dormancy. The juçara seeds vigor was evaluated by the plantules height and dry weight. In the standard germination test, the Biomatic germinator was used at a constant temperature of 30°C. The experimental delineation was that of blocks with 4 repetitions of 50 seeds and 8 treatments, the same was used for the "juçara seeds conservation and viability" experiment and for pre-germinative treatments conducted on the murici seeds. For the germination in germitest paper and sand with macerated seeds for 24 and 48 hours at 42°C, it was used the blocks delineation, by chance, with 4 repetitions of 50 seeds and 4 treatments. In the bacaba seeds sowing position experiment, the results were compared by the F Test. The bacurizinho, and murici germination results, were transformed into arc senVx when null values occurred. The averages comparison was carried out by the the Tukey Test at 5% of probability. The fruits and seeds biometiy was gotten by the standard deviation average in agreement with the characteristic of the variable. On the germination in different substrata for juçara with 72,5% of germination, the best results were gotten with litter + TP, on the fírst evaluation and 93.5% on the second evaluation and for the bacurizinho it was gotten 66.7% of germination in the same substratum. The plants growth presented significant differences among the substrata, except for the Fava D’anta and litter + TP, which presented averages of 11,7% and 11,6% respectively not differing among themselves. The germination in sand with seeds that were macerated for 24 and 48 hours with and without pulp, presented significant differences in relation to the maceration time and removal of the pulp, with averages of 84% and 93%. However the standard germination test in sand with seeds that were macerated for 24 and 48 hours, presented significant differences, the highest gotten average was that of 45% of germination in seeds without rind that were macerated by 48 hours. The results gotten on the plants growth and weight of diy substance of seeds that were macerated for 24 and 48 hours tests, resulted in significantly different averages, the highest average on the plants height was that of 11,33 cm with seeds with no rind that were macerated for 48 hours and with the weight of 2l9mg of dry substance. The storage demonstrated some differences among the germination averages: seeds with rind dried for 10 days, 65,5%; seeds with no rind dried for 10 days, 56,0%, seeds with no rind dried for 15 days presented the average of 46,5; and the seeds with and without rind dried for 20 days, stored in refrigerator for more 20 days, presented 58.5% and 41,5% respectively. The murici seeds presented the best average in the dung substratum + TP, in the pre-germinative treatments with sulfuric acid at 25% during 60 minutes.